Multiscale assembly of polyoxometalates: From clusters to materials - Boyuan Yu; Xin Zhao; Jiangfeng Ni; Feng Yang (ChemPhysMater, 2023)
ABSTRACT: Polyoxometalates (POMs) have drawn broad and intense interest due to their unique structure-dependent properties. The assembly of POM molecules into nanoarchitectures and superstructures can bridge the gap between micro-molecule and bulk POM materials and integrate the merits of molecule and materials that are widely used in catalysis, energy conversion, electronics, and bioapplications. The synthetic methodologies and applications of multiscale POM assemblies have been widely studied. In this review, we survey the POM-based multiscale assembly focusing on two aspects: the strategies for multiscale assembly of POMs and the emerging applications of POM assemblies. For the multiscale assembly, we focus on the methods of POMs assembly including templated synthesis and self- and co-assembly of POMs into nanoarchitectures and superstructures. For the applications, we review the applications of POM assemblies in energy, catalysis, and functional materials. Finally, we present the prospects for the future synthetic design and applications of POM assemblies.